IDENTICAL TWIN FEMALE CALVE BORN IN FIELD CONDITION - Singh Saini, Nishant; Kumar, Amit; Bisht, Sapna; Yadav, Kamal Kant (International Journal of Research -GRANTHAALAYAH, 2015)
A repeat breeder crossbred cow was presented to clinic and after treatment with this condition animal was come in heat with clear mucous than artificial insemination was done and animal become pregnant and regularly monitoring health of the animal than delevered twin female calf after artificial insemination.